A Innovative Technology-Based Coffee Agro-Industry Development Strategy to Increase Farmers' Competitiveness in Kare District, Madiun Regency - Nur Indah, Pawana; Widayanti, Sri; Indah Harya, Gyska; Setiawan, Risqi Firdaus (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
This research aims to develop a strategy for developing innovative technology-based coffee agroindustry in Kare District, Madiun Regency. The application of modern technology, such as roasting and wet processing, has proven to improve robusta coffee's quality and added value and increase competitiveness in the domestic and international markets. In addition, empowering farmers through training and technical assistance is key to improving their skills in post-harvest technology management. The research method used is mixed-method, with qualitative and quantitative approaches. Data was obtained through a survey with a Likert scale questionnaire, in-depth interviews, field observations, and documentation. SWOT analysis evaluates the strengths, weaknesses, opportunities, and threats in developing coffee agroindustry in the region. The study results show that the coffee industry in Kare District has significant strengths and opportunities, although it still faces challenges related to capital and technology limitations. The recommended strategies are product diversification, institutional capacity building, and more intensive promotion, as well as the development of coffee agro-tourism as a step to improve farmers' welfare and expand market access